Recognition of human front face in Grayscale Images - Mohamed Rizon, Mohamed Juhari; Phaklen Ehkan; Ahmad Nasir, Che Rosli (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th-19th May 2005 at Putra Palace Hotel, Kangar